Venetoclax and Azacitidine Combination is an Effective Salvage Regimen for Fit Patients with IDH-2-mutated Acute Myeloid Leukemia Refractory to Conventional Induction Chemotherapy - Musa Fares Alzahrani (Journal of Applied Hematology)
Acute myeloid leukemia (AML) constitutes a heterogeneous group of clonal myeloid neoplasms that is associated with a large number of recurrent genetic abnormalities. Mutations in IDH2 gene can be found in nearly 10% of newly diagnosed AML patients. The impact of IDH2 mutations on prognosis in the absence of other genetic abnormalities remains to be unclear in fit patients although recently believed to be favorable in less fit patients receiving less intensive therapy. Enasidenib, which is an IDH2 inhibitor, was recently developed, but it is currently not widely available and it is only approved in the relapsed or refractory setting. Moreover, fit patients with AML who fail to respond to conventional induction chemotherapy represent a high-risk group in whom the only potential cure is allogeneic stem cell transplantation (AlloSCT), which is ideally performed after achievement of complete remission following treatment with a salvage regimen. Previous studies have shown efficacy of venetoclax combination with azacitidine (VenAza) in newly diagnosed unfit patients. It is still unknown if VenAza is an effective salvage regimen for fit IDH2-mutated AML patients who fail to respond to traditional chemotherapy. Here, we report two cases with IDH2-mutated AML, both of whom salvaged successfully with VenAza, which allowed bridging to the definitive treatment of AlloSCT.